2003
DOI: 10.1073/pnas.1534925100
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization by selection: Generation of a metallosupramolecular grid architecture by selection of components in a dynamic library of ligands

Abstract: Self-organization by selection is implemented in the generation of a tetranuclear [2 ؋ 2] grid-type metallosupramolecular architecture from its components. It occurs through a two-level self-assembly involving two dynamic processes: reversible covalent bound connection and reversible metal ion coordination. Thus, mixing the aminophenol 3, the dialdehyde 4, and zinc acetate generates the grid complex 1a(Zn) via the assembly of the ligand 2a by imine formation and of the grid by zinc(II) binding. When the same p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
64
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(67 citation statements)
references
References 41 publications
0
64
0
3
Order By: Relevance
“…Determination of T gel as a function of the concentration of 1 for different cations showed that K ϩ was the most efficient gelator͞G 4 assembler. The other cations showed the sequence of gelation efficiency Me 4 N ϩ Ͼ NH 4 ϩ Ͼ Na ϩ (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Determination of T gel as a function of the concentration of 1 for different cations showed that K ϩ was the most efficient gelator͞G 4 assembler. The other cations showed the sequence of gelation efficiency Me 4 N ϩ Ͼ NH 4 ϩ Ͼ Na ϩ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It generates constitutional dynamic libraries (CDLs) whose constituents are in dynamic equilibrium, such that they can exchange their components and express all of the entities that are potentially accessible through recombination by means of reversible covalent bonds and noncovalent interactions. The CDL may then adapt to (internal or) external physical factors or chemical effectors by selection (3,4) of the appropriate components for the optimal constituent. Such processes form the basis of the recently developed dynamic combinatorial chemistry (5,6), in which molecular recognition events have been implemented toward the generation of optimal binding agents toward artificial or biological (7) molecular receptors through a target-driven shift in the distribution of the library constituents toward the best binder(s).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following the proposition that such self‐organization processes are equally responsible for the dynamic generation of molecular and supramolecular diversity and complexity in three‐dimensional (3D) bulk structures,12, 13, 14, 15 we herein report on the complexation of a homoditopic ligand with two tridentate chelates with iron(II) and the accompanying tautomerism‐driven emergence of complexity. Whereas a number of ligands with tridentate chelates and tautomeric subunits have previously been described,16, 17, 18, 19, 20 we are not aware of any examples that describe the presence of different tauto‐conformers and the parallel formation of isomeric reaction products.…”
mentioning
confidence: 99%
“…This ''subcomponent self-assembly'' has its roots in the template synthesis of Busch and coworkers (16) and has recently been used in the synthesis of a wealth of structures, including rotaxanes (17), catenanes (18), helicates (19)(20)(21)(22), grids (23)(24)(25), and a Borromean link (26). These structures belong to the domains of both dynamic covalent (27) and supramolecular (28) chemistry and offer a particularly rich set of possibilities for dynamic rearrangement at both covalent and dative linkages (29).…”
mentioning
confidence: 99%